Exploring effective strategy to improve grade VI-VIII science - Choden, Dechen (International Journal of Humanities and Education Development (IJHED), 2020)
The study explored the most effective strategy to improve science in Classes VI-VIII. The researcher selected relevant topics from the science textbooks of classes VI to VIII and taught them using three strategies: demonstration, experimentation and ICT/Video lesson. Paper pencil tests were conducted after completion of each strategy and the mean test scores were compared with the pre-test score. The study employed a mixed mode approach. The data were collected from Classes VI-VIII students (N= 15 from each class) using survey questionnaire and structured interview. The post intervention test score, survey and interview reports revealed that students’ interest in learning science is spurred through hands[1]on experiments.